DISCOURSE OF MUSLIM CONSUMER RATIONALITY AL-GHAZALI'S KNOWLEDGE PARADIGM PERSPECTIVE - Imamudin Yuliadi; Eko Prasojo (ASIAN PUBLISHER, 2026)
Islamic beliefs and values shape Muslim consumer behavior. Islamic beliefs and values control a person's behavior. This paper identifies the concept by tracing Al-Ghazali's thoughts regarding the rationality of Muslim consumers from a set of Islamic principles: prioritizing needs, maintaining sharia goals, complying with halal and haram rules, prioritizing sustainable consumption, prioritizing the benefit of individuals and society, and not consuming excessively. A text analysis approach is used to map studies on Muslim consumer behavior. Apart from that, a historical-critical and inductive approach was used to identify the concepts and opinions of ulama regarding Islamic rationality and Al-Ghazali's thoughts. The findings provide important benefits in developing the theory of Islamic rationality, which can then be used as an alternative in explaining Muslim consumer behavior and can also be a reference for stakeholders in the industry to mainstream the calcification of products offered in the Muslim market. Islamic rationality is different from the economic rationality put forward by neoclassical economics. Like the model proposed by Al-Ghazali, Islamic rationality places the human heart as an instrument for forming patterns of economic behavior.